PELATIHAN OPIMALISASI APLIKASI MEDIA PEMBELAJARAN BERBASIS GOOGLE (GMEET, GCLASROOM, GFORM) DI TAMAN KEBALEN - Dina Safitri; Abdul Ghofur; Rabiyannur Lubis (An-Nizam, 2022)
Currently, almost everyone uses the sophistication of technology that is growing among children, parents, and even everyone. With the very rapid development of technology such as the latest, latest, and very effective applications in the online learning process today. In the environment, there are still many who do not understand how to use applications that have been provided by technology experts. So with learning media application training to make work easier and the target of achieving understanding can be achieved by relying on sophisticated and not boring technology. Through this training, it will be a reference for further learning using learning application media and the results can increase knowledge and information about learning media applications, can increase confidence in the community in developing application media for learning.